2020
DOI: 10.17116/hirurgia202009128
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid aortic repair in patients with type III aortic dissection and concomitant proximal aortic lesion

Abstract: В настоящее время метод выбора хирургического лечения пациентов с осложненным расслоением аорты III типа по DeBakey с сочетанным поражением дуги или восходящего отдела аорты не определен. Представляем наш опыт гибридного подхода с использованием методики Frozen Elephant Trunk (FET) для лечения таких больных. Материал и методы. В период с января 2010 по август 2019 г. в РНЦХ им. акад. Б.В. Петровского выполнено 90 (28,3%) операций FET, из них в 19 случаях показанием к вмешательству являлось расслоение B-типа в … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…The mean follow up time was 16 months and 14.5 months respectively for group one and two. This study contradicts Kreibich et al ( 9 ) study, as it provides a direct comparison between devices and confirms Thoraflex Hybrid™ superiority over E-Vita ( 32 ). Only one study looking at E-Vita Open device reported a relatively low dSINE occurrence of 1% of a patient population of 286.…”
Section: Distal Stent Induced New Entrycontrasting
confidence: 80%
See 4 more Smart Citations
“…The mean follow up time was 16 months and 14.5 months respectively for group one and two. This study contradicts Kreibich et al ( 9 ) study, as it provides a direct comparison between devices and confirms Thoraflex Hybrid™ superiority over E-Vita ( 32 ). Only one study looking at E-Vita Open device reported a relatively low dSINE occurrence of 1% of a patient population of 286.…”
Section: Distal Stent Induced New Entrycontrasting
confidence: 80%
“…Terumo Aortic's Thoraflex TM Hybrid is an excellent FET device with very favorable survival outcomes that are to some extent superior to those offered by other commercially available devices. The incidence of dSINE with Thoraflex Hybrid TM can be considered the lowest within the aortic arch prostheses market as demonstrated above (9,20,24,25,(31)(32)(33)(34)(35)(36)(37).…”
Section: Distal Stent Induced New Entrymentioning
confidence: 96%
See 3 more Smart Citations